Розвиток утоми muscle soleus у результаті його тривалої активації при розвитку ішемічної контрактури - Зай, Світлана; Матвієнко, Тетяна; Білобров, Владислав; Парадізова, Софія; Вулицька, Дарія; Мотузюк, Олександр; Zay, Svitlana; Matvienko, Tetyana; Bilobrov, Vladyslav; Paradizova, Sofiya; Vulits’ka, Daryna; Motuzyuk, Oleksandr (Східноєвропейський національний університет імені Лесі Українки, 2017)
У роботі досліджували процес розвитку м’язової втоми при ішемічних патологіях. Аналіз проводився визначенням сили на початку та в кінці поодиноких тетанічних скорочень і різниці між цими величинами. Результати досліджень показали, що при розвитку ішемічних контрактур відбувається значне пригнічення скоротливої активності скелетних м’язів. Установлено, що порушення скоротливої здатності скелетних м’язів виникає внаслідок нехолінергічних ефектів цієї патології The process of muscle fatigue development under ischemic pathologies was studied. The analysis was performed determining the muscle force level at the beginning and end of single tetanic contractions and the difference between these values, which determines the dynamic component of force decrease during a short period of continuous stimulation. We also calculated the time reduction of the contractions force down to 50 % and 30 % of the initial level. The muscle was considered tired if the amplitude of the single tetanic contractions decreased by more than 50 % relative to the initial level. The muscle insufficiency to support a significant force of the tetanic contractions demonstrated influence on the contractile activity of ischemic damage and the differences between molecular mechanisms of the force generation and the development of muscle fibers dynamic process. Differences in muscle contraction during the studied stages can be explain by the difference in the process of filaments interaction at tetanic and pre-tetanic contractions and the influence of the membranes of muscle connective tissue changes on these processes under pathology conditions. The results showed that during development of ischemic contractures there is a significant inhibition of contractile activity of skeletal muscles. It was established that a disfunction of skeletal muscles contractile ability is a result of the noncholinergic effects of this disease.
Rozvitok Vtomu M'yazy Kambalovydnoy v Rezul'tate Eho Trivaloyi Aktivatsiyi Pry Rozvytku Ishemichnoyi Kontraktury
Keywords: м’язова втома; muscle soleus; м’язове скорочення; алкогольна інтоксикація; muscle fatigue; muscle contraction; alcohol intoxication